Regulating the Right to Be Forgotten in Indonesia’s Digital Banking: Lessons from the EU GDPR - Librawenson, Winco; Disemadi, Hari Sutra; Afdal, Windi (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The implementation of the right to be forgotten in digital banking transactions in Indonesia faces complex legal challenges. Legal disharmony among regulations on personal data protection, electronic information and transactions, and banking law creates uncertainty in applying this right. This study aims to evaluate the legal framework of the right to be forgotten in Indonesia and compare it with the European Union's General Data Protection Regulation (GDPR) to identify an ideal normative solution. The research employs a normative legal method with statutory and comparative approaches. The findings indicate that the GDPR provides a more flexible data deletion mechanism, including the existence of an independent supervisory authority and simpler procedures for individuals to request data erasure. To enhance legal certainty in regulating the right to be forgotten in Indonesia, legal reform is necessary. This includes harmonizing existing regulations, formulating technical guidelines for Electronic System Providers (ESPs), and establishing an independent Personal Data Protection Authority similar to the European Data Protection Board (EDPB).